Posterior chain flexibility and lower back pain in farm workers - Marcia Regina da Silva; Lucimare Ferraz; Fátima Ferretti; Cristiane Sfredo
Abstract Introduction: Flexibility is an essential component of physical aptitude that reduces the incidence of muscle distention and improves movement efficiency and posture. Objective: To analyze posterior chain flexibility and lower back pain (LBP) in farm workers from a city in western Santa Catarina state, Brazil. Methods: Quantitative and cross-sectional study conducted with 185 rural workers, average age of 44.24 (±10.83) years. The Rural Worker Health Questionnaire, containing individual issues related to work; sit and reach box, goniometer, visual analog scale (VAS) and Oswestry and Roland-Morris questionnaires were used to evaluate posterior chain flexibility, hamstring muscle length, pain and lumbar spine dysfunction, respectively. Flexibility was compared with the degree of dysfunction using one-way ANOVA followed by the Bonferroni post hoc test. Results: 181 (97.8%) workers reported LBP symptoms: 100% of the women and 95.2% of the men. The average Oswestry score was 7.09 (±8.25), Roland-Morris 1.22 (±1.63), and VAS 5.81 (±2.5). Average flexibility by the sit and reach test (SRT) was 23.91cm (±18.81); straight leg raise (SLR), 66° (±11.77) and popliteal angle 123.21° (±12.45). There was a significant difference in the popliteal angle (p = 0.003) and SLR (0.001) when compared with the degree of dysfunction. Women showed significant differences in all tests; however, the post hoc test showed a significant difference only in the SRT (p = 0.013), and women with minimal dysfunction had greater flexibility in relation to those with severe dysfunction. Conclusion: Self-reported LBP was severe and women with higher levels of dysfunction exhibited less posterior chain flexibility.